A compensatory approach to fuzzy fractional transportation problem. (1st January 2014) - Radhakrishnan, Bheeman; Anukokila, Paraman
In this paper, we establish the fuzzy fractional transportation problem with compensatory approach. To illustrate the proposed compensatory approach to fuzzy fractional transportation problem by using Werner's 'fuzzyor' ( μor ) operator. We construct optimal solution by using fuzzy Vogel's approximation method. A numerical example has been provided to illustrate the problem.